1995
DOI: 10.1002/ijc.2910630409
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic segregation of HTLV‐I and HTLV‐II carriers among South American native Indians

Abstract: To investigate the genetic background of human T-cell leukemia virus type I (HTLV-I) and II (HTLV-II) carriers among South American native Indians, we analyzed HLA DRB1*-DQB1* haplotypes of the virus carriers from Andes highlands and Orinoco lowlands by the PCR-RFLP genotyping method. It was revealed that the HTLV-I-carrying Andes natives had one of the 5 HLA haplotypes: DRB1*-DQB1* 0403-0302, 0802-0402, 0901-0303, 1406-0302 and 0407-0302, and that the Orinoco HTLV-II carriers had one of the 3 HLA haplotypes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
1
14
0
2
Order By: Relevance
“…Hence, recent introductions from other populations seem unlikely considering that the efficiency of transmission of this virus is considerably low. Our suggestion has been supported by the presence of this virus among different native inhabitants in North and South America [Fujiyoshi et al, 1995;Kaplan et al, Fig. 3.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Hence, recent introductions from other populations seem unlikely considering that the efficiency of transmission of this virus is considerably low. Our suggestion has been supported by the presence of this virus among different native inhabitants in North and South America [Fujiyoshi et al, 1995;Kaplan et al, Fig. 3.…”
Section: Discussionsupporting
confidence: 75%
“…In these countries, HTLV-I has been found in various ethnic populations, including whites, blacks, mestizos, mulattoes and Japanese immigrants. It should be noted that the presence of HTLV-I has also been identified among native inhabitants of South America (Amerindians) in Argentina [Bouzas et al, 1994], Colombia [Duenas-Barajas et al, 1992;Zaninovic et al, 1994], Chile [Cartier et al, 1993;Fujiyoshi et al, 1995], and Brazil [Ishak et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Host genetic background including human leukocyte antigen (HLA) genotype, and HTLV-I proviral load are thought to predict the risk of these diseases among HTLV-I carriers (Usuku et al, 1988;Bangham, 2003). The genetic background of HTLV-I carriers (South America native Indians and individuals living in Andes highlands and Orinoco lowlands) was investigated, and the results suggested that HLA haplotypes might be ethnically segregated and might be involved in the susceptibility to HTLV-I infection (Fujiyoshi et al, 1995). High levels of HTLV-I proviral load may be associated with HTLV-I diseases; however, risk factors for high proviral load are uncertain (Takenouchi et al, 2003;Murphy et al, 2004a).…”
Section: Adult T-cell Leukemiamentioning
confidence: 99%
“…Among Colombian native Indians, a high prevalence of human T-cell lymphotropic virus-type I (HTLV-I), HTLV-II [Zaniovic et al, 1994;Fujiyoshi et al, 1995], and GB virus C (GBV-C) Asian type [Tanaka et al, 1998], which are mainly found in the Asian population, has been noted. A high prevalence of TTV is found in Japan [Okamoto et al, 1998].…”
Section: Introductionmentioning
confidence: 99%